Augmented Reality as a Digital Pedagogical Tool to Support Adaptive Speaking Practice in ELT - Fakhrurriana, Ria; Safitri, Silviana (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2025)
As digital technology is more embedded in English Language Teaching (ELT), it continues to offer new ways to support learners to build their English-speaking skills. This study is meaningful, as speaking is known as one of the most challenging aspects for English learners, and Augmented Reality (AR) offers a promising tool to control this issue by creating interactive and immersive environments. The main point addressed in this study is the learners’ problems in improving their speaking abilities due to limited vocabulary, low confidence, and lack of real conversation practice. The goal of this study is to investigate how Augmented Reality (AR) supports speaking skill development and what certain aspects it enhances. This study utilized a Systematic Literature Review (SLR) approach, examining 30 recent scholarly articles. The evidence reveals that Augmented Reality (AR) positively supports speaking skill acquisition by increasing learner confidence, stimulating interaction, improving fluency, and offering realistic communicative contexts. This paper extends the literature on digital learning tools by highlighting the pedagogical potential of AR in ELT. It provides appropriate guidance for language teachers and encourages further research to explore the effective ways of implementing AR in English language speaking skills.